Comparative Study of Yttria Stabilized Zirconia Prepared by Co-precipitation Method using Various Precursors and its Potential as Gas Sensor - Khaladkar M.Y.; Purandare R.R. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Yttria stabilized zirconia (YSZ) have different chemical properties. These include excellent chemical resistance, refractory character, oxygen ionic conductivity and polymorphism. Due to these properties, YSZ finds many structural and electronic applications such as gas sensors, electrolyte and anode in SOFC’s, dental implants and thermal barrier coatings. These interesting properties and resultant applications primarily require stabilized zirconia in tetragonal and cubic crystal structure. In present paper, synthesis of stabilized zirconia using 8 mol percent yttria was carried out by co-precipitation method. Various precursors like hydroxide, oxalate and citrate were used for the same. The phase formation was studied using X-ray Diffractometry and the surface morphology by scanning electron microscopy. The pellets were used for sensing gases like oxygen, nitrogen, hydrocarbons and NOx etc. The response obtained for all the pellets is discussed at length. It is observed that, YSZ obtained from oxalate precursor gives better response.